The Relationship Between Social Media Engagement, Clean Habits, Smoke-Free Environment, School Environment, Parenting, And Students' Healthy Lifestyle (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This study aims to investigate the intricate relationship between social media engagement, clean habits, smoke-free environment, school environment, parenting, and students' healthy lifestyle. Utilizing a phenomenological research model, data will be collected through purposive sampling involving students, parents, and educators. Thematic analysis will be employed to discern patterns and themes from the collected data. The study seeks to reveal the interplay of these factors in shaping students' health behaviors and lifestyle choices. Findings are anticipated to offer insights into the multifaceted influences on students' health, informing strategies for promoting healthier lifestyles within educational settings.